Study of interfacial reaction between Cu and Pb-free solders and rapid temperature cycling methodology for reliability assessment - Chen, Binling (2008)
The global objective of this research endeavor is to inhibit the excessive growth of IMC and improve the properties of Sn-Ag-Cu lead-free solder alloy by adding small mount of Sb.